Implementation of Modeling Training to Optimize Children’s Talent Potential in Elementary Education - Hilda Restu Umi; Alis Triena Permanasari; Dwi Junianti Lestari (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze the implementation of a modeling training program in optimizing the talent potential of elementary school students at Rossy’s Entertainment. The background of this study is based on the importance of developing non-academic talents as part of fostering character, self-confidence, and social skills in children from an early age. The study employs a qualitative approach using the case study method. Data collection techniques include observation, in-depth interviews with trainers and students, and documentation of training activities. Data analysis was conducted interactively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the modeling training program was implemented systematically through stages covering an introduction to the basics of modeling, training in catwalk techniques and facial expressions, as well as mental strengthening and building self-confidence. This program has proven effective in optimizing children’s potential, particularly in terms of self-confidence, communication skills, and self-expression. Furthermore, the role of professional trainers and a supportive training environment were key factors contributing to the program’s success. These findings confirm that modeling training can serve as an alternative strategy for the holistic development of children’s talents. The implications of this research are expected to serve as a reference for nonformal educational institutions in designing innovative and sustainable programs for the development of children’s talents.